2022
DOI: 10.1088/2399-1984/ac3ccd
|View full text |Cite
|
Sign up to set email alerts
|

Study of the tribological properties of nano lubricating oil blends for diesel engines

Abstract: This paper is to evaluate and compare the tribological properties of lubricating oil blends added with nano graphene and lubricating oil blends added with cerium oxide (CeO2) on the key friction pairs of the diesel engines. The dispersion stability is the premise of studying the tribological properties. In this paper, nano-CeO2 particles were self-made and high-quality nano-graphene was purchased. The dispersion stability of the two nanomaterials in lubricating oil was studied after the same modification respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Finally, the oil soluble graphene was obtained by centrifugal drying after being stirred for 4 h at 80 °C. Previous experimental results 27 have shown that the dispersion stability of the modified graphene lubricating oil was improved, and the modified graphene lubricating oil with 25 ppm concentration had the best tribological properties. The modified nano-graphene with a mass concentration of 25 ppm was weighed into the lubricating oil by a precision balance.…”
Section: Test Device and Methodsmentioning
confidence: 85%
See 2 more Smart Citations
“…Finally, the oil soluble graphene was obtained by centrifugal drying after being stirred for 4 h at 80 °C. Previous experimental results 27 have shown that the dispersion stability of the modified graphene lubricating oil was improved, and the modified graphene lubricating oil with 25 ppm concentration had the best tribological properties. The modified nano-graphene with a mass concentration of 25 ppm was weighed into the lubricating oil by a precision balance.…”
Section: Test Device and Methodsmentioning
confidence: 85%
“…Through the measurement of Digital Micrograph software, it can be seen that the average thickness of nano-graphene is about 0.5–1 nm, and the number of nano-graphene layers is about 1–3. Nano-graphene was chemically modified by oleic acid and stearic acid in the following ways 27 . Firstly, 0.5 g of nano-graphene was dispersed into 100 mL anhydrous ethanol.…”
Section: Test Device and Methodsmentioning
confidence: 99%
See 1 more Smart Citation